On Yukawa Couplings in the Zee-Babu Model - Long, Hoang Ngoc; Vien, Vo Van (Communications in Physics, 2013)
The exact solution for neutrino mass matrix of the Zee-Babu modelis derived. The tribimaximal mixing imposes the conditions on the Yukawa couplings, from which the normal mass hierarchy ispreferred. The derived conditions give a possibility of maximal \(CP\) violation in the neutrino sector.